Building trust and recovery capital: the professionals' helpful practice. Issue 2 (23rd April 2018) - Topor, Alain; Skogens, Lisa; von Greiff, Ninive
Abstract : Purpose: The possibility of recovery for persons with co-occurring addiction and mental health problems has been contested. Though, recent studies show that recovery might happen, but without connection to specific treatment interventions. The purpose of this paper is to analyse professionals' perceptions of their contribution to improvement. Design/methodology/approach: In all, 15 experienced professionals were interviewed. The interviews were analysed using thematic analysis. Findings: Recovery processes were dependent of the persons' access to different forms of recovery capital (RC). Lack of RC was often associated with lack of trust in one's self and others (identity and personal capital). Professionals had to be accepted as trustful agents through co-creating changes in the person's life. Trusting a professional might be a basis for trusting one's self as an agent in one's recovery process and develop a social network (identity and relationship capital). Other aspects stressed by the professionals were to manage their own fragmentized organisations and societal shortcomings (economic capital). Practical implications: Recovery has been described as a profoundly individual journey. However, it is also deeply social, involving other persons and contextual factors. Focusing on just one level might counteract the complex work behind double recovery. Originality/value: Improvement was described as dependent on the presence of personal, inter-personal, organisational and societal factors. The findings give a deep and concrete understanding of the process constituting the development of a working alliance and its dependence on factors outside the direct relation between the staff member and the person.